45.1k views
1 vote
2x+y= 3

x-2y= -1
If equation two is multiplied by -2, and then the equations are added, the result is

2x+y= 3 x-2y= -1 If equation two is multiplied by -2, and then the equations are added-example-1
User Jigberto
by
6.0k points

1 Answer

1 vote

Answer:

5y = 5

Explanation:

When the second equation is multiplied by -2, it becomes ...

-2(x -2y) = -2(-1)

-2x +4y = 2

Adding this to the first equation gives ...

(2x +y) +(-2x +4y) = (3) +(2)

2x +y -2x +4y = 5 . . . . . . . . . eliminate parentheses

5y = 5 . . . . . . . . . . . . . . . . . . .collect terms

User Leshane
by
5.9k points